1997
DOI: 10.1055/s-2007-994095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Theophylline on Renal Function in Premature Infants

Abstract: Xanthines are frequently being used in the management of premature babies. Studies in adult subjects have demonstrated a diuretic effect of aminophylline due to the inhibition of solute reabsorption in various segments of the nephron. We evaluated the effects of aminophylline on the developing kidney. Nineteen premature infants, with a mean +/- SD gestational age of 31.1 +/- 2.8 weeks and mean birth weight of 1481 +/- 454 g were studied at mean age of 4.5 +/- 4.0 days before and after a 20-minute loading infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
(24 reference statements)
2
18
1
Order By: Relevance
“…Infants who received frusemide [16,17] and theophylline [18,19] had significantly higher UCa/Cr as previously reported. Infants on dexamethasone also had higher UCa/Cr, but this did not achieve statistical significance, in contrast to the data of Kamitsuka et al [20], perhaps because of the relatively small numbers in this study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Infants who received frusemide [16,17] and theophylline [18,19] had significantly higher UCa/Cr as previously reported. Infants on dexamethasone also had higher UCa/Cr, but this did not achieve statistical significance, in contrast to the data of Kamitsuka et al [20], perhaps because of the relatively small numbers in this study.…”
Section: Discussionsupporting
confidence: 77%
“…A recent retrospective study of babies born at <37 weeks gestation reported that the incidence of NC was 0.73% (1.7% for VLBW infants) [15]. Factors known to influence UCa excretion in the preterm infant include frusemide [16,17], theophylline [18,19], and dexamethasone [20]. Furosemide has also been shown to increase UPO 4 excretion in VLBW infants [17].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in urine calcium and sodium excretion was previously reported in prema tures treated with theophylline during 4 weeks postnatal age by Rowe et al [9], Furthermore, Mazkereth et al [10] found a similar effect in prematures 24 h after a loading aminophylline dose, which was associated with an in crease in urine FeNa. Our study design showed hypercalciuria with the use of both methylxanthine derivatives theophylline and caf- feine, after a 5-day course.…”
Section: Discussionsupporting
confidence: 58%
“…As a result, the renal blood flow and glomerular filtration rate decrease, leading to the occurrence of NC. 32,33 In this study, the duration of theophylline treatment was significantly longer in the NC group in the univariate analysis, but not in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 52%